PENGARUH PEMBERIAN HIDROKUINON TERHADAP PERKEMBANGAN FETUS MENCIT (MUS MUSCULUS L.) SWISS WEBSTER - Rubiyati Rubiyati; Arum Setiawan (Universitas Baiturrahim, 2016)
Background : Hydroquinone is natural substance chemistry that were using by cosmetics as bleachers skin. The creams contains of more than >2% hydroquinone could cause irritation in the skin. In long usage will caused skin bluish black and ochronosis. The aims of this study is to find the effect of hydroquinone to the fetus development. Method : The research about the influence of hydroquinone to the mouse fetal development has been done on February – April 2014 at The Research Center (LPPT) Gadjah Mada University Yogyakarta. This research used randomized complite design 5 treatment and 5 replicated. The datas were analyzed with one way Anova and then with Duncan’s test. Hydroquinone administrated intraperitoneal injection at a dosage 10 mg/kgbw, 20 mg/kgbw, 30 mg/kgbw in 6 days of gestation. The remaining animals were used as an untreated control, and placebo were given by aquades. at 18th days of gestations, twenty five pregnant mice were sacrificed and caesarian sectioned to remove the fetuses and then check fetus body wight, life fetus, dead fetus and morfology fetus. The results showed that administration of hydroquinone to pregnant mice decreased the average number of fetuses, fetal weight, and implantation. The congenital malformation that caused by administration of hydroquinone were neural tube defects, anotia, microtia, Intra Uterine Fetal Defects, limb defects, tail defects.It was concluded that hydroquinone administrated to the pregnant mice inhibits the fetal growth, decreased the number of fetal and increased malformation of fetal.Keywords : Hydroquinone, Mice, Fetal, Malformation, NTDs